Keep Safe, Keep Learning: Principals' Role in Creating Psychological Safety and Organizational Learning During the COVID-19 Pandemic - Weiner, Jennie; Francois, Chantal; Stone-Johnson, Corrie; Childs, Joshua (Frontiers in Education, 2021)
Utilizing a sample of 54 interviews from a larger study of traditional public school principals’ responses to the COVID-19 pandemic, we examined the degree to which principals in 19 states and representing both urban (e.g., intensive, emergent or characteristic) (Milner, 2012) (n=37) and suburban settings (n=17) and across all student levels (i.e., elementary, middle, and high), experienced and engaged in behaviors to create psychological safety during the COVID-19 pandemic. We also sought to understand how various environmental and organizational features may have influenced these conditions and thus the likelihood of learning taking place. We find principals reported varied levels of psychological safety in their schools with associated differing levels of organizational learning and responsiveness to the crisis. However, rather being grounded in environmental conditions (e.g., urbanicity, demographics, etc.), organizational factors and specifically, differences in accountability, principal autonomy, professional culture and teacher decision-making were all key in the degree of psychological safety exhibited. Together, these findings serve to expand understanding of leadership as creating conditions for learning and give insight into the degree our pre-COVID-19 system may have facilitated or stymied the ability or capacity of school leaders in different settings to support transformational learning. In this way, this research may have real and important implications for the types of support leaders and teachers require as we collectively transition into the next phase of uncertainty as many schools continue to try and re-open safely and all that lays ahead.